Keputusan Pembelian Produk Whitening/Brightening - Nabilla Arza Ramadhani; Noor Faidah; Ruth Natalia Susanti (PT PUSTAKA CENDEKIA GROUP, 2025)
This study examines the impact of brand image and digital marketing on skin lightening product purchase decisions among young people in Kudus Regency. The use of skin lightening products is increasing, influenced by psychological, social, and digital factors, particularly through social media and influencer reviews. The study used descriptive qualitative methods with simple quantitative data, with a sample of 20 university students aged 14 to 20. The results indicate that digital promotion and brand image are the primary factors influencing skin lightening product purchase decisions. Purchase motivation is dominated by social and emotional factors, such as the desire for acceptance by the community and increased self-confidence, rather than solely the product's benefits. These findings provide important insights for local cosmetics marketing strategies and improving consumer understanding.